The Existing Framework of Environmental Accounting and Sustainable Finance across the Globe - Kamaran Abdulla, Shene Mohammad; Ali, Hazhar Khalid (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
Environmental accounting is the branch that recognizes the application of resources, estimates, and interprets the costs of an organization or the influence it has on the environment economically. The costs cover the expenses related to cleaning up and reforming the contaminated areas, penalties, and taxes, procurement of technologies to reduce or prevent pollution, also expenses related to waste management and environmental fines. Therefore, environmental accounting can be referred to as a subgroup of accounting proper that aims include information and details regarding both economics and the environment. Further, this accounting structure consists of conventional accounting that is environmentally distinguished as well as ecological accounting. This paper is concerned with understanding, reviewing, and determining the existing framework for environmental accounting and sustainable finance across the globe and recommending the best possible methods to increase the effectiveness of such standards.